2009
DOI: 10.1159/000245042
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Calcifications in End-Stage Renal Disease Patients: A New Link between Osteoprotegerin, Diabetes and Body Mass Index?

Abstract: The aim of the study was to assess the factors potentially involved in coronary artery calcifications (CAC) in end-stage renal disease patients. 253 hemodialysis (HD) patients (92 females, 161 males), aged 62.5 ± 13.5, who had been on HD treatment for at least 6 months, were enrolled in a cross-sectional study. Calcium-phosphate product (Ca × P), body mass index (BMI), fetuin-A, osteoprotegerin (OPG), osteopontin, transforming growth factor-β1 (TGF-β1), fibroblast growth factor-23 (FGF-23) and matrix Gla prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 123 publications
5
15
1
Order By: Relevance
“…Because MGP is a potent inhibitor of vascular calcifications [1, 2, 4], some authors have suggested that the protein may be useful in the monitoring or even the detection of vascular calcifications in CKD or HD subjects [25, 35]. In the present study, we confirmed a significant correlation between dp-ucMGP levels and the calcification score in the univariate analysis and this association was confirmed in the multivariate model.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Because MGP is a potent inhibitor of vascular calcifications [1, 2, 4], some authors have suggested that the protein may be useful in the monitoring or even the detection of vascular calcifications in CKD or HD subjects [25, 35]. In the present study, we confirmed a significant correlation between dp-ucMGP levels and the calcification score in the univariate analysis and this association was confirmed in the multivariate model.…”
Section: Discussionsupporting
confidence: 87%
“…This positive correlation between dp-ucMGP levels and the calcification score supports however the theoretical role of MGP in the development of vascular calcifications. It also advocates the need for additional studies, particularly with other active isoforms of MGP [7, 22, 32, 3539]. For instance, total uncarboxylated MGP (which may be partially bioactive) has been negatively associated with coronary calcification in dialysis patients [36].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, calcium score was inversely correlated with FGF-23 and BMI. FGF-23 showed a signi�icant inverse correlation with CAC in univariate analysis but it was not an independent predictive factor of CAC in multivariate analysis [30]. Conversely, Roos et al [31] reported no association between CAC and FGF-23 levels in patients with normal kidney function.…”
Section: Discussionmentioning
confidence: 91%
“…Since calcium and phosphorus are each raised above adult normal values, fetal blood has a high calcium x phosphorus product (Ca x P) that may facilitate spontaneous calcium-phosphate crystals to form and cause soft tissue calcifications. In adults, a Ca x P value Ͼ5.6 mmol 2 /l 2 or 70 mg 2 /dl 2 is associated with calciphylaxis, coronary artery calcifications, and increased mortality (58,115,126,724). However, this level may be needed to mineralize the fetal skeleton and may be nonhazardous in utero due to its relatively short duration.…”
Section: Human Datamentioning
confidence: 99%